ANALISIS SOSIAL EKONOMI PENGELOLAAN HASIL HUTAN DAMAR (Agathis Dammara) DI DESA RAMBATU, KECAMATAN INAMOSOL, KABUPATEN SERAM BAGIAN BARAT - Maslebu, Odri Tara; Silaya, Thomas; Parera, Evelin (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The objectives of this study were to determine the social aspects of resin forest product management, analyze the level of community income in managing resin forest products and determine the contribution of resin forest product income in Rambatu village, Inamosol sub-district, West Seram Regency. This study applied the survey method to collect data from a specific location, namely Rambatu village, using questionnaires and direct interviews with individuals and groups at the research site. The results of the study revealed that the community of Rambatu Village coexists with resin tree species that have become an additional source of income for the local community. By paying attention to the level of community income in managing resin forest products by striving for management without depleting the results of resin trees in Rambatu village and reviewing the contribution of income from resin forest products which is quite helpful to the community's economy, namely 30.52%, this is smaller than the side income of the community reaching 69.48%. Therefore, the management process must cooperate with related parties such as the Vocational Training Center (BLK) to seek the development of knowledge and skills in managing resin forest products properly and correctly and seek a better sales concept between resin workers and collectors so that the income of the Rambatu community increases.